Perancangan Sistem Informasi Inventory Dengan V-Model Berbasis Web Pada PT Brickbern - Robinsar Naibaho (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
PT BrickBern is a distribution company specializing in LEGO (Leg Godt) toy products. An efficient inventory information system is crucial for managing the diverse range of LEGO products and enables the company to meet customer demand effectively. The V-Model method was chosen as a structured development approach due to its advantages in well-defined development and testing stages, allowing for early error detection and correction. The research began with a needs analysis that included an in-depth understanding of the company's requirements for LEGO product inventory management. The system design phase followed, covering database design, user interface design, and adequate system architecture. Subsequently, the system was implemented and tested, and training was provided to users. The research outcome is a web-based inventory information system that supports PT BrickBern in managing LEGO product inventory more efficiently and in real-time, thereby enhancing PT BrickBern's operational efficiency in distributing LEGO products and increasing customer satisfaction. Furthermore, these findings can serve as a reference for similar companies looking to develop web-based inventory information systems using the V-Model method.